'I kind of figured it out': the views and experiences of people with traumatic brain injury (TBI) in using social media—self‐determination for participation and inclusion online. Issue 2 (5th June 2018) - Brunner, Melissa; Palmer, Stuart; Togher, Leanne; Hemsley, Bronwyn
Abstract: Background: Social media can support people with communication disability to access information, social participation and support. However, little is known about the experiences of people with traumatic brain injury (TBI) who use social media to determine their needs in relation to social media use. Aims: To determine the views and experiences of adults with TBI and cognitive‐communication disability on using social media, specifically: (1) the nature of their social media experience; (2) barriers and facilitators to successful use; and (3) strategies that enabled their use of social media. Methods & Procedures: Thirteen adults (seven men, six women) with TBI and cognitive‐communication disability were interviewed about their social media experiences, and a content thematic analysis was conducted. Outcomes & Results: Participants used several social media platforms including Facebook, Twitter, Instagram and virtual gaming worlds. All but one participant used social media several times each day and all used social media for social connection. Five major themes emerged from the data: (1) getting started in social media for participation and inclusion; (2) drivers to continued use of social media; (3) manner of using social media; (4) navigating social media; and (5) an evolving sense of social media mastery. In using platforms in a variety of ways, some participants developed an evolving sense of social media mastery. Participants applied caution in using social media, tended to learn through a process of trial and error, and lacked structured supports from family, friends or health professionals. They also reported several challenges that influenced their ability to use social media, but found support from peers in using the social media platforms. This information could be used to inform interventions supporting the use of social media for people with TBI and directions for future research. Conclusions & Implications: Social media offers adults with TBI several opportunities to communicate and for some to develop and strengthen social relationships. However, some adults with TBI also reported the need for more information about how to use social media. Their stories suggested a need to develop a sense of purpose in relation to using social media, and ultimately more routine and purposeful use to develop a sense of social media mastery. Further research is needed to examine the social media data and networks of people with TBI, to verify and expand upon the reported findings, and to inform roles that family, friends and health professionals may play in supporting rehabilitation goals for people with TBI.